L'archivio del Regio Istituto delle Signore Montalve alla Quiete di Firenze Inventario (1812-2000) - Giagnoni, Nicola (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2022)
The Royal Institute of Signore Montalve alla Quiete was born between 1885 and 1886, by the union of the two congregations founded by the venerable Eleonora Ramirez de Montalvo: the Montalve di Ripoli and the Montalve alla Quiete. From them inherits the principles and the educational action carried out for over two centuries, bringing them to the threshold of the new millennium. In this analytical inventory are described the papers produced by the new Institute. The core relating to female education is only one of the subjects that this archive can offer: architectural and social transformations, the two world wars, customs and traditions of population are just some examples of the researchs offered and the Tuscan historical frame that the cards draw in a well-defined way.